Docetaxel-induced hand and foot syndrome in a patient with metastatic breast carcinoma - Ravichandran Gurumurthi; Ramesh BV Nimmagadda; Subhashini Mohan (Wolters Kluwer Medknow Publications, 2013)
Hand and foot syndrome (HFS) is a well-known complication of chemotherapeutic drugs given in a dose-dense manner. Our patient was a 52-year-old female with metastatic breast carcinoma on salvage chemotherapy regimen with docetaxel at a dose of 60 mg/m 2 . The patient had grade 3 HFS characterized by symmetrical, tender, and erythematous skin lesions over the palms and soles associated with dysesthesia necessitating interruption of treatment. She developed this syndrome at a much lower dose than previously described due to her altered hepatic function. An insight regarding this unique distressing side-effect and assessment of various contributing factors would help us identify and treat the patient at the earliest.